1999
DOI: 10.1016/s0014-5793(99)01635-x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix regulation of PTHrP and PTH/PTHrP receptor in a human breast cancer cell line

Abstract: It was previously reported that 8701-BC breast cancer cells express the gene for parathyroid hormone-related peptide (PTHrP) and its cognate receptor (PTHrP-R), and release immunoreactive PTHrP in the extracellular medium; it was also found that PTHrP, in turn, exerts a role on the proliferative and invasive behavior in vitro of the same cell line. On the other hand, evidence has been produced that adhesion of 8701-BC cells onto different collagen substrates influences in various ways a number of phenotypic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
(42 reference statements)
1
19
0
Order By: Relevance
“…18 In contrast, when ROS 17/2.8 cells were treated with DEX for 6 and 24 h, the specific binding of 125 I-PTHrP-1-36 was increased, but when the same cells were treated with progesterone the effect of DEX on PTH/PTHrP-R expression was diminished. 19 There are some comparable data from KPL-3C and MCF7 cell lines on the effect of phorbol ester, steroid hormones, anti-estrogens and extracellular matrix (ECM) [26][27][28][29] but no reports on the effects of EGF, 1,25DHCC and DEX on PTH/PTHrP-R protein or gene expression in breast cancer cells. Nevertheless the data here suggest an additional mechanism by which the use of vitamin D analogues may act to suppress the proliferation of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…18 In contrast, when ROS 17/2.8 cells were treated with DEX for 6 and 24 h, the specific binding of 125 I-PTHrP-1-36 was increased, but when the same cells were treated with progesterone the effect of DEX on PTH/PTHrP-R expression was diminished. 19 There are some comparable data from KPL-3C and MCF7 cell lines on the effect of phorbol ester, steroid hormones, anti-estrogens and extracellular matrix (ECM) [26][27][28][29] but no reports on the effects of EGF, 1,25DHCC and DEX on PTH/PTHrP-R protein or gene expression in breast cancer cells. Nevertheless the data here suggest an additional mechanism by which the use of vitamin D analogues may act to suppress the proliferation of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The similar adhesion capability of NCI-H520 cells on two different matrices indicates that adhesion of these cells is mediated by multiple types of integrins. Reported interactions between PTHrP and extracellular matrix include regulation of collagen synthesis by PTHrP in chondrocytes, and extracellular matrix modulation of PTHrP promoter usage, mRNA splicing patterns, and extent of extracellular release (Luparello et al, 1999;Goomer et al, 2000). A recent study showed that the increased production of PTHrP in stable transfectants of a human colon cancer cell line significantly enhanced cell adhesion to type I collagen, raising the possibility that PTHrP is involved in colon tumor invasion and metastasis (Ye et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer was one of the original tumors from which PTHrP was purified and sequenced [17], and it is now known that it is a key factor controlling bone homing and resorption by metastasizing breast cells [2]. Some of us have reported that PTHrP expression by neoplastic breast cells ''in vitro'' is drastically modulated by modifications of the culture microenvironment [18,19]; in addition, data have been produced demonstrating that different PTHrP domains are also biologically-active on breast tumour cells in culture [20][21][22]. In particular, PTHrP (38-94)-amide, administered at 1 nM concentration was found able to restrain growth and invasion as well as to cause striking toxicity and accelerate death of a panel of breast cancer cell lines, the most responsive being MDA-MB231.…”
Section: Introductionmentioning
confidence: 99%